2015
DOI: 10.1159/000368387
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Incus Vibroplasty in Patients with Moderate-to-Severe Sensorineural Hearing Loss

Abstract: Objectives: The principal aim of this study was to assess the safety and effectiveness of the middle ear implant Vibrant Soundbridge (VSB) in patients with moderate-to-severe sensorineural hearing loss up to a mean (± standard deviation) duration of 11.1 ± 2.1 years (min. = 8.2, max. = 13.9, n = 16) after the intervention. Design: This was a retrospective, single-subject repeated-measurements study over a long-term period. A total of 104 German-speaking adults (for 122 implants) were included in this study (54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
11
1
2
Order By: Relevance
“…Individual results of each coupler group were as follows: RW = 43 dB, OW = 35 dB, Bell = 37 dB, CliP = 27 dB. These values exceed clinically significant improvement, measured at 15 dB HL [Maier et al, 2015]. The average preoperative unaided and postoperative aided free-field thresholds, respectively, at the frequencies 0.5, 1, 2 and 4 kHz for each coupler group in dB HL were as follows: RW = 75.44 and 32.06, OW = 76.79 and 41.60, CliP = 60.00 and 32.90, Bell = 73.40 and 36.60.…”
Section: Audiometric Resultsmentioning
confidence: 71%
“…Individual results of each coupler group were as follows: RW = 43 dB, OW = 35 dB, Bell = 37 dB, CliP = 27 dB. These values exceed clinically significant improvement, measured at 15 dB HL [Maier et al, 2015]. The average preoperative unaided and postoperative aided free-field thresholds, respectively, at the frequencies 0.5, 1, 2 and 4 kHz for each coupler group in dB HL were as follows: RW = 75.44 and 32.06, OW = 76.79 and 41.60, CliP = 60.00 and 32.90, Bell = 73.40 and 36.60.…”
Section: Audiometric Resultsmentioning
confidence: 71%
“…Similar rates were found for other studies using vibroplasty couplers for FMT positioning (4.4-22%) [Busch et al, 2016;Ihler et al, 2014;Zhao et al, 2016]). In addition, VSB implantation with conventional incus or round window vibroplasty concluded revision rates between 3.8 and 18.8% [Gregoire et al, 2018;Maier et al, 2015;Marino et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] To date, a few studies focused on long-term audiological or surgical outcomes. Maier et al 7 reported on audiological outcomes in 104 patients and 122 devices implanted in a single center. A study group led by Sterkers et al 8 reported on 125 patients implanted with the VSB, analyzing patient satisfaction using self-assessment scales postoperatively.…”
Section: Introductionmentioning
confidence: 99%